Implications of Franchise Agreements for Default by Franchisees (Case Study: Decision Number 1064K /PDT/2020) - Masni Purba; Martono Anggusti; Roida Nababan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the rapid growth of the franchise business in Indonesia, which has prompted the government to regulate and protect the legal relationship between franchisors and franchisees through various regulations, including Government Regulation Number 42 of 2007 and the Ministry of Trade Regulation Number 71 of 2019. A dispute case between PT MYSalon International as the franchisor and Ratnasari Lukitaningrum as the franchisee highlights the challenges in implementing franchise agreements in Indonesia. This research was conducted qualitatively with a case study analysis. The research method used is empirical juridical. The case study analysis and literature review are described in this research. The main challenges in franchise agreements include unclear contract clauses, non-compliance with regulations, lack of trust, and operational difficulties in implementing franchisor standards. The impact of these challenges includes lawsuits, contract termination, and damage to business reputation. Based on civil law principles such as consensualism, freedom of contract, and good faith, this study emphasizes the importance of compliance with regulations and transparency in the implementation of franchise agreements to create justice and business sustainability. The study concludes that harmonizing regulations and simplifying administrative processes are necessary to address the challenges in franchise agreements in Indonesia while promoting healthy and competitive franchise sector growth.